(untitled) (Research, Society and Development, 2020)
In the current context of a global pandemic, distance education has been identified as a quick solution to the challenges of higher education. This proposal disregards the enormous complexity of the planning and implementation process of this modality, when carried out with quality. Among the main needs is a rigorous teacher training process. This article presents the research, development and evaluation of a training course, guided by the TPCAK, for teachers who worked in the undergraduate course in biological sciences, semi-presential modality at the Federal University of Santa Catarina (UFSC), Brazil. We analyzed the records of activities and comments in the virtual environment of the course, a semi-open questionnaire and a meeting with the participants. The results indicate that the course allowed the experimentation of tools linked to the discussions about the teaching of the disciplines, offering the possibility of overcoming the instrumental vision of technological means. The experience mainly encouraged reconsideration of the teacher’s role, in a transition to more activity-centered teaching. We discussed that the integration of TDIC is not reduced to the selection and use of technological resources, but is achieved through a process of articulating the potential of these tools to the knowledge and knowledge of teachers in the development of educational possibilities for their teaching contexts. This requires investment of time and qualified professionals, but allows the development of teaching mediated by TDIC that prioritizes the quality of student training in university contexts.